Highly porous structure, manufacturing methods thereof, and lithium secondary batteries containing the same
Patent Information
- Application Number
- KR1020240114521
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2044-08-26
Smart Images

Figure R1020240114521_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a lithium metal electrode, and more specifically, to a porous structure for a lithium metal electrode, a method for manufacturing the same, and a lithium secondary battery including the same. Background Technology
[0002] Much effort has been devoted to developing high-capacity anode materials (lithium metal) to increase the energy density of batteries, and they are attracting attention as promising candidate materials due to their high specific capacity and low reduction potential. Unfortunately, however, lithium dendrites caused by severe volume changes during battery operation and side reactions resulting from high reactivity remain the most persistent problems hindering their practical application as high-capacity anodes. Non-uniform movement of lithium ions leads to ion aggregation and the formation of lithium dendrites. These lithium dendrites, in turn, cause charge and electron aggregation, eventually coming into contact with the anode to cause internal short circuits, acting as a major risk factor to battery stability. Furthermore, low Coulomb efficiency due to side reactions and the formation of thick solid electrolyte interfaces (SEIs) lead to a rapid decrease in capacity.
[0003] To address these issues, developments have been made regarding the introduction of a protective layer on lithium metal, electrodeposition of lithium metal within structures, and the formation of a stable SEI through electrolyte modification. Among these, the strategy of electrodepositing lithium metal onto structures increases the specific surface area, thereby lowering local potential and facilitating the stable electrodeposition of lithium metal within the structure. However, most structures utilize metals such as copper or nickel, which presents limitations due to their high cost and heavy weight. Furthermore, a problem persists where, in cases where the top surface of the structure has high electronic conductivity, the lithium metal is deposited on the top surface during electrodeposition, degrading functionality. The problem to be solved
[0004] The objective of the present invention is to provide a porous structure that lowers local potential and enables uniform lithium metal movement, is lightweight, and has low manufacturing costs.
[0005] Another objective of the present invention is to provide a method for manufacturing a porous structure that has the aforementioned advantages, is simple to manufacture, and allows for easy control of the pore size.
[0006] Another objective of the present invention is to provide a lithium secondary battery having high energy density capable of high-speed charging by including a porous structure having the aforementioned advantages. means of solving the problem
[0007] A porous structure according to one embodiment of the present invention comprises a lithium-affinity polymer, a three-dimensional structure, and pores, wherein the pores satisfy a full width at half maximum (FWHM) of the pore distribution graph of 0.01 to 1.0 μm.
[0008] The porosity of the above porous structure may be 40 to 75%.
[0009] The porosity of the above porous structure may be 60 to 75%.
[0010] The above porous structure can satisfy the following Equation 1.
[0011] [Equation 1]
[0012] 0 μm ≤ D 70 -D 30 ≤ 0.50 μm
[0013] (D of Equation 1 above I In this, I is the integral value of the above pore distribution graph from 0 μm, and D I is the pore diameter at the point satisfying I.)
[0014] The above porous structure can satisfy the following Equation 2.
[0015] [Equation 2]
[0016] 0 μm ≤ D 80 -D 20 ≤ 0.80 μm
[0017] (D of Equation 2 aboveI In this, I is the integral value of the above pore distribution graph from 0 μm, and D I is the pore diameter at the point satisfying I.)
[0018] The diameter at the maximum peak of the above pore may be 0.05 to 0.5 μm.
[0019] The diameter at the maximum peak of the above pore may be 0.3 to 0.5 μm.
[0020] The thickness of the above porous structure may be 5 to 60 μm.
[0021] A method for manufacturing a porous structure according to another embodiment of the present invention comprises: (S1) a step of preparing a slurry by mixing and stirring a lithium-affinity polymer, a conductive material, and a solvent; (S2) a step of applying the slurry onto a substrate; and (S3) a step of forming a porous structure by placing the substrate coated with the slurry into a water bath containing a non-solvent, wherein R of the non-solvent HSP The value of (Hansen solubility parameter distance) satisfies between 25 and 29.
[0022] The above slurry may comprise 3 to 20 weight percent of the lithium-affinity polymer, 0.4 to 2 weight percent of the conductive material, and the remainder being a solvent, based on 100 weight percent of the total.
[0023] R of the above cost solvent HSP The value of can satisfy 25 to 27.
[0024] The above material may include at least one of a current collector and a porous material.
[0025] A lithium metal electrode according to another embodiment of the present invention comprises a porous structure and a lithium metal, wherein the lithium metal is located in at least one of the inside and outside of the porous structure and satisfies the following Equations 3 and 4.
[0026] [Equation 3]
[0027] 1 ≤ LME / HCA ≤ 1.3
[0028] [Equation 4]
[0029] -1 ≤ △y / △x ≤ 1
[0030] (In Equation 3 above, LME is the cross-sectional thickness of the lithium metal electrode, and HCA is the cross-sectional thickness of the porous structure, and
[0031] In the above Equation 4, x is the position from left to right of the cross-section of the lithium metal electrode, and y is the height of the lithium metal electrode at x, and
[0032] △y / △x is the ratio of the change in y to the change in x.
[0033] The above lithium metal electrode can satisfy the following Equations 5 and 6.
[0034] [Equation 5]
[0035] 1 ≤ H2 / H1 ≤ 1.2
[0036] [Equation 6]
[0037] 1 ≤ v2 / v1 ≤ 7
[0038] (H in Equation 5 above n Silver is the thickness of the cross-section of the lithium metal electrode after lithium charging, and
[0039] In Equation 6 above, v n Silver thickness H n It is the lithium charging rate of the lithium metal electrode having the above, and as n increases, v n The value of is large.)
[0040] The above porous structure may include a porous structure according to one embodiment of the present invention described above.
[0041] A lithium secondary battery according to another embodiment of the present invention comprises: a positive electrode; a negative electrode; and an electrolyte located between the positive electrode and the negative electrode, wherein the negative electrode comprises a porous structure according to one embodiment of the present invention described above. Effects of the invention
[0042] The porous structure according to an embodiment of the present invention is composed of a polymer having lithium-friendly characteristics and has a structure for electrodepositing lithium metal in the pores, thereby lowering the local potential and enabling uniform movement of lithium metal. In addition, it prevents the formation of lithium dendrites and has a low manufacturing cost. In particular, it is lightweight and can be utilized in lithium secondary batteries having high energy density.
[0043] A method for manufacturing a porous structure according to another embodiment of the present invention has the aforementioned advantages and allows for easy control of the thickness of the porous structure and the internal pore size through a non-solvent-induced phase separation method.
[0044] A lithium secondary battery according to another embodiment of the present invention includes a porous structure having the aforementioned advantages, thereby effectively suppressing volume expansion and having a high energy density capable of high-speed charging and discharging. Brief explanation of the drawing
[0045] FIG. 1 is a cross-sectional view briefly illustrating a method for manufacturing a lithium metal electrode according to one embodiment. Figure 2 is a scanning electron microscope (SEM) image confirming the porosity of the porous structures of Example 1, Example 2 and Comparative Example 1. Figure 3 is a graph showing the porosity of the porous structures of Example 1, Example 2, and Comparative Example 1. Figure 4 is a graph showing the ionic and electronic conductivity of the porous structures of the examples and comparative examples. FIGS. 5 and 6 show Example 1 and Comparative Example 2 at 1, 3, and 5 mAh / cm², respectively. 2 This is an SEM image of a cross-section of a lithium metal electrode filled with lithium. FIGS. 7 and 8 show Example 1 and Comparative Example 2 at 1 mA / cm 2 This is an SEM image of a lithium metal electrode charged with lithium at a rate. FIGS. 9 and 10 show Example 1 and Comparative Example 2 at 5 mA / cm 2 This is an SEM image of a lithium metal electrode charged with lithium at a rate. Figure 11 is a graph of the charge-discharge cycles of the asymmetric lithium batteries of Example 1, Example 2, and Comparative Example 2. Figure 12 is a graph of the charge-discharge cycles of the LFP lithium full batteries of Example 1 and Comparative Example 2. Figure 13 is a graph of the charge-discharge cycles of the NCM lithium full battery of Example 1 and Comparative Example 2. Specific details for implementing the invention
[0046] The technical terms used herein are for the reference of specific embodiments only and are not intended to limit the invention. The singular forms used herein include plural forms unless phrases clearly indicate otherwise. As used in the specification, the meaning of "comprising" specifies certain characteristics, areas, integers, steps, actions, elements, and / or components, and does not exclude the presence or addition of other characteristics, areas, integers, steps, actions, elements, and / or components.
[0047] Unless otherwise defined, all terms used herein, including technical and scientific terms, have the same meaning as generally understood by those skilled in the art to which this invention pertains. Terms defined in commonly used dictionaries are further interpreted to have meanings consistent with relevant technical literature and the present disclosure, and are not interpreted in an ideal or highly formal sense unless otherwise defined.
[0048] In this specification, the term “combination(s) of these” described in the Markush-type expression means one or more mixtures or combinations selected from the group consisting of the components described in the Markush-type expression, and means including any one or more selected from the group consisting of said components.
[0049] Hereinafter, embodiments of the present invention will be described in detail. However, these are presented as examples and are not intended to limit the present invention, and the present invention is defined only by the scope of the claims set forth below.
[0050] porous structure
[0051] As mentioned above, conventional lithium metal electrodes have problems such as reduced capacity, heavy weight, and volume expansion. To solve this, the present embodiment provides a porous structure using a lithium-affinity polymer and a non-solvent-induced phase separation method.
[0052] FIG. 1 is a cross-sectional view briefly illustrating a method for manufacturing a lithium metal electrode according to one embodiment.
[0053] The thickness of the porous structure can be 10 to 90 μm. Specifically, the thickness of the porous structure can be 10 to 85 μm, 15 to 80 μm, or 20 to 75 μm. By satisfying the aforementioned ranges for the thickness of the porous structure, it is possible to ensure the stability of the porous structure and provide a high-energy-density lithium secondary battery.
[0054] As the thickness of the porous structure exceeds the upper limit of the aforementioned range, the thickness of the lithium metal electrode (400) becomes excessively thick, which may hinder the manufacture of a high-energy-density lithium secondary battery. Additionally, as the lower limit of the aforementioned range is exceeded, there is a problem in that the stability of the porous structure is reduced.
[0055] The porous structure is 0.2 to 0.6 × 10⁻⁶ -2It can have an electron conductivity of S / cm. Specifically, 0.25 to 0.55 × 10⁻⁶ -2 S / cm, 0.3 to 0.55×10 -2 S / cm, 0.35 to 0.50×10 -2 It can be S / cm. Since the electronic conductivity of the porous structure satisfies the aforementioned range, the lithium metal (300) can be easily positioned inside or outside the porous structure.
[0056] As the electronic conductivity of the porous structure exceeds the upper limit of the aforementioned range, the lithium metal (300) accumulates on the surface of the porous structure, causing a problem of volume expansion. Additionally, as it exceeds the lower limit of the aforementioned range, it may hinder the lithium metal (300) from being located inside or outside the porous structure.
[0057] In addition, the difference in ionic conductivity between the porous structure and the Cu foil is 0.1×10⁻⁶ -3 It may be greater than S / cm. Specifically, ionic conductivity refers to the ionic conductivity of the electrolyte impregnation, and the porous structure may have a higher ionic conductivity than the Cu foil due to the high contact area resulting from the three-dimensional structure (220) and pores (230) of the second porous structure (200) to be described later, and due to the lithium-affinity polymer that is the constituent material. Specifically, the difference in ionic conductivity is 0.12 × 10⁻⁶ -3 S / cm, 0.14×10 -3 S / cm, 0.16×10 -3 S / cm, 0.18×10 -3 S / cm, 0.2×10 -3 It may be S / cm. By satisfying the upper limit range of the difference in ion conductivity, smooth ion exchange between the electrolyte and the lithium metal electrode (400) becomes possible, thereby increasing the efficiency of the lithium secondary battery. If the difference in ion conductivity does not reach the value mentioned above, there is a problem in that the lithium metal electrode (400) has an efficiency similar to that of a Cu foil.
[0058] Referring to FIG. 1, the porous structure includes a first porous structure (100) and a second porous structure (200). The first porous structure (100) is in the form of a thin film and is located below the second porous structure (200). The first porous structure (100) can function as a current collector and can serve as a support for the formation of the second porous structure (200). Through this form and function, the local potential of the lithium metal electrode (400) is lowered, and the lithium metal (300) can move smoothly. However, this is an example according to one embodiment, and the porous structure may include at least one of a current collector and a porous substrate in addition to the first porous structure (100), and is not limited to the form and function described above. In this case, the current collector may specifically be a metal layer such as copper, stainless steel, aluminum, nickel, etc., and may be a metal layer having a conductive coating layer such as a carbon black-based coating layer on its surface. The above porous substrate may have a porous structure composed of a polymer or a metallized polymer, etc.
[0059] The thickness of the first porous structure (100) may be 5 to 40 μm. Specifically, the thickness of the first porous structure (100) may be 10 to 35 μm, 15 to 30 μm, or 20 to 25 μm. By satisfying the aforementioned ranges for the thickness of the first porous structure (100), the stability of the porous structure can be secured and a high-energy-density lithium secondary battery can be provided.
[0060] As the thickness of the first porous structure (100) exceeds the upper limit of the aforementioned range, the thickness of the lithium metal electrode (400) becomes excessively thick, which may hinder the manufacture of a high-energy-density lithium secondary battery. Additionally, as the thickness exceeds the lower limit of the aforementioned range, there is a problem in that the stability of the porous structure is reduced.
[0061] The first porous structure (100) may include carbon nanotubes (CNTs). The first porous structure (100) may include 90% or more of the CNTs with respect to 100% of the total weight.
[0062] The above CNT may be at least one of SWCNT (single-walled carbon nanotube) and TWCNT (thin-walled carbon nanotube). However, it is not limited to the aforementioned materials, and any material capable of performing a similar effect and role may be applied.
[0063] The second porous structure (200) may be positioned on the first porous structure (100). In this case, the first porous structure (100) may be replaced with at least one of a current collector or a porous substrate as described above. The second porous structure (200) may include the aforementioned lithium-affinity polymer, a conductive material, the aforementioned CNT, a three-dimensional structure (220), and pores (230).
[0064] The second porous structure (200) includes the above configuration to lower the local potential of the lithium metal electrode (400) and allow the lithium metal (300) to move smoothly. In addition, it is lightweight, has a low manufacturing cost, and can have the effect of preventing the formation of lithium dendrites. Furthermore, its lightweight nature can contribute to high energy density lithium secondary batteries.
[0065] In addition, the difference in electron conductivity between the first porous structure (100) and the second porous structure (200) is 0.2×10 -2 It may be greater than S / cm. Specifically, the above difference in electron conductivity is 0.25 × 10⁻⁶ -2 S / cm, 0.30×10 -2 S / cm, 0.35×10 -2 S / cm, 0.40×10 -2 S / cm, 0.45×10 -2It may be S / cm. By satisfying the upper limit range of the difference in electron conductivity, the first porous structure (100) can effectively perform the role of a current collector. If the difference in electron conductivity does not reach the value of the aforementioned value, there is a problem that the first porous structure (100) has lower efficiency compared to a commercially available metal current collector.
[0066] The second porous structure (200) may comprise 3 to 20 weight% of a lithium-affinity polymer, 0.4 to 2 weight% of a conductive material, 0.05 to 0.5 weight% of CNTs, and the remainder being pores (230) based on 100 weight% of the total. Specifically, the second porous structure (200) may comprise, with respect to 100 weight% of the total, 4 to 18 weight%, 5 to 16 weight%, 6 to 14 weight%, 7 to 12 weight% of a lithium-affinity polymer, 0.5 to 1.8 weight%, 0.6 to 1.6 weight%, 0.7 to 1.4 weight% of a conductive material, 0.06 to 0.45 weight%, 0.07 to 0.40 weight%, 0.08 to 0.35 weight%, 0.09 to 0.30 weight%, 0.1 to 0.25 weight% of CNTs, and the remainder being pores (230). By satisfying the weight percentage of the lithium-affinity polymer, conductive material, and CNT as described above, the effect of achieving a uniform three-dimensional structure (220), pores (230), and porosity of the second porous structure (200) and ensuring stability is achieved.
[0067] As the weight percentage of the lithium-affinity polymer, conductive material, and CNT exceeds the upper limit of the aforementioned range, the density and compactness of the second porous structure (200) increase, making it difficult to secure space for the lithium metal (300) to be located or move, or hindering it. As a result, the limit on the amount of lithium metal (300) electrodeposited inside the structure is drastically reduced, and there is a problem in that the aforementioned advantages cannot be achieved. Additionally, as it exceeds the lower limit of the aforementioned range, the compactness and mechanical stability of the second porous structure (200) may be reduced.
[0068] Lithium-affinity polymers are ionic polymers capable of affinity and electrical interconnection with lithium, and may include PVA (Polyvinyl alcohol, PVA), Polyacrylic acid (PAA), Polyacrylonitrile (PAN), Polymethyl methacrylate (PMMA), Poly(vinyl pyrrolidone) (PVP), Agar, Chitosan, Polyimide (PI), Polyethylene terephthalate (PET), Poly(ethyleneimine) (PEI), etc.
[0069] The conductive material helps bond between the lithium-affinity polymer and the CNT, increases strength, and allows the lithium metal (300) to move smoothly. The conductive material is not particularly limited as long as it is conductive without causing chemical changes in the battery. Specifically, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fibers such as carbon fiber or metal fiber; metal powder such as carbon fluoride, aluminum, or nickel powder; conductive whiskey such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive materials such as polyphenylene derivatives may be used.
[0070] The thickness of the second porous structure (200) may be 5 to 80 μm. Specifically, the thickness of the first porous structure (100) may be 10 to 85 μm, 15 to 80 μm, 20 to 75 μm, 25 to 70 μm, or 30 to 65 μm. By satisfying the aforementioned ranges for the thickness of the second porous structure, a space for sufficiently charging the lithium metal (300) can be secured, and this can contribute to the manufacture of a high-energy-density lithium secondary battery.
[0071] If the thickness of the second porous structure (200) exceeds the aforementioned upper limit value, the thickness of the lithium metal electrode (400) becomes excessively thick, which may hinder the manufacture of a high-energy-density lithium secondary battery. Additionally, if the value exceeds the lower limit of the aforementioned range, the stability of the porous structure is reduced, and there is a problem in that the lithium metal (300) cannot be sufficiently charged.
[0072] The second porous structure (200) may include a three-dimensional structure (220) and pores (230). The three-dimensional structure (220) is a structure formed by combining a lithium-affinity polymer, a conductive material, and CNTs, and its shape is not limited. Pores (230) are formed through the three-dimensional structure (220), and lithium metal (300) can be located or moved in the pores (230). By having lithium metal (300) located or moved in the pores (230), lithium dendrite growth and volume expansion of the lithium metal electrode (400) can be prevented.
[0073] Referring to FIG. 3, which will be described later, the second porous structure (200) may have a porosity of 40 to 75%. Specifically, the porosity may be 45 to 75%, 50 to 75%, 55 to 75%, 60 to 75%, 65 to 75%, or 70 to 73%. By satisfying the aforementioned ranges, a sufficient amount of lithium metal (300) can be stored, thereby contributing to the manufacture of a high-energy-density lithium secondary battery. If the porosity deviates from the upper limit of the aforementioned ranges, there is a problem in that the lithium metal (300) cannot be overcharged or positioned stably, and thus lithium dendrite growth and volume expansion cannot be prevented. In addition, if the lower limit value of the aforementioned range is exceeded, the amount of lithium metal (300) being charged is insufficient, which lowers the capacity of the lithium secondary battery, and there is a problem in that the remaining lithium metal (300) that is not located inside the porous structure promotes dendrite growth on the surface of the porous structure.
[0074] The diameter of the above pore (230) may have a single steep and narrow peak in the pore distribution graph. This can be represented by the full width at half maximum (FWHM), which is a term indicating the width of the graph and, in the present invention, is defined as the difference in pore diameter at a position that is half the maximum peak of the pore distribution graph. The full width at half maximum of the pore distribution graph may be 0.01 to 1.0 μm. Specifically, the full width at half maximum may be 0.02 μm, 0.9 μm, 0.03 to 0.8 μm, 0.04 to 0.7 μm, 0.05 to 0.6 μm, or 0.06 to 0.5 μm. By satisfying the above ranges for the full width at half maximum, the lithium metal (300) can be positioned or moved within the pore (230) of a constant diameter, thereby preventing lithium dendrite growth and volume expansion of the lithium metal electrode (400). As the above half-width deviates from the upper and lower limits of the aforementioned range, there is a problem in that the diameter of the pore (230) is not uniform, and thus the aforementioned advantage cannot be achieved.
[0075] In addition, the above pore distribution graph may satisfy at least one of the following Equation 1 or Equation 2.
[0076] [Equation 1]
[0077] 0 μm ≤ D 70 -D 30 ≤ 0.50 μm
[0078] (D of Equation 1 above I In this, I is the integral value of the above pore distribution graph from 0 μm, and D I is the pore diameter at the point satisfying I.)
[0079] Satisfying Equation 2 below,
[0080] [Equation 2]
[0081] 0 μm ≤ D 80 -D 20 ≤ 0.80 μm
[0082] (D of Equation 2 above I In this, I is the integral value of the above pore distribution graph from 0 μm, and D I is the pore diameter at the point satisfying I.)
[0083] The above Equations 1 and 2 indicate that the second porous structure (200) has a distribution of pores (230) of uniform diameter. In other words, the second porous structure (200) satisfying the above Equations 1 and 2 means that the internal pores (230) mostly have similar diameters, thereby containing a uniform three-dimensional structure (220).
[0084] The above Equation 1 may have a value of 0 to 0.50 μm. Specifically, it may be 0 to 0.45 μm, 0.01 to 0.40 μm, 0.02 to 0.35 μm, 0.03 to 0.30 μm, or 0.04 to 0.25 μm. The above Equation 2 may have a value of 0 to 0.80 μm. Specifically, it may be 0 to 0.75 μm, 0.02 to 0.70 μm, 0.04 to 0.65 μm, 0.06 to 0.60 μm, or 0.08 to 0.55 μm. By satisfying the aforementioned ranges of Equations 1 and 2, a uniform diameter distribution of pores (230) is achieved, allowing the lithium metal (300) to be stably positioned or moved, thereby preventing lithium dendrite growth and volume expansion of the lithium metal electrode (400). However, if Equations 1 and 2 deviate from the upper and lower limits of the aforementioned ranges, the diameter distribution of the pores (230) is not uniform, which results in a problem where the aforementioned advantages cannot be achieved.
[0085] The diameter at the maximum peak on the pore distribution graph of the pore (230) may be 0.05 to 0.5 μm. Specifically, it may be 0.1 to 0.5 μm, 0.15 to 0.5 μm, 0.2 to 0.5 μm, 0.25 to 0.45 μm, or 0.3 to 0.4 μm. By satisfying the above-mentioned ranges for the porosity and the pore (230), a space is secured in which the lithium metal (300) can be located or moved within the second porous structure (200), thereby preventing lithium dendrite growth and volume expansion of the lithium metal electrode (400).
[0086] There is a problem in that the above porosity and pores (230) exceed the upper limit of the aforementioned range, causing the lithium metal (300) in the second porous structure (200) to be consumed quickly or the stability of the second porous structure (200) to be reduced. Additionally, there is a problem in that the above advantages cannot be achieved because it is difficult to secure a space for the lithium metal (300) to be located or move within the second porous structure (200) when the above-mentioned lower limit of the aforementioned range is exceeded.
[0087] The difference in electron conductivity between the first porous structure (100) and the second porous structure (200) is 0.2×10 -2 It may be greater than S / cm. Specifically, 0.25×10 -2 S / cm, 0.3×10 -2 S / cm, 0.35×10 -2 S / cm, 0.4×10 -2 S / cm, 0.45×10 -2 S / cm, 0.5×10 -2 S / cm, 0.55×10 -2 It may be S / cm. By satisfying the upper limit range of the above-mentioned value for the difference in electron conductivity, the first porous structure (100) can smoothly perform its role as a current collector. If the difference in electron conductivity does not reach the above-mentioned value, the first porous structure (100) has difficulty performing its role as a current collector, which causes a problem of reducing the efficiency of the lithium metal electrode (400).
[0088] The difference in CNT weight% between the first porous structure (100) and the second porous structure (200) may be in the range of 60 to 90 weight%. Specifically, it may be 65 to 85 weight% or 70 to 80 weight%. By satisfying the above range for the difference in CNT weight%, an appropriate difference in density and density is formed between the first porous structure (100) and the second porous structure (200). Through this, the bonding portion between the first porous structure (100) and the second porous structure (200) is stably bonded, thereby providing the advantage of improving the stability and electronic conductivity of the porous structure. If the difference in CNT weight% deviates from the upper and lower limits of the above range, there is a problem in that the bonding force between the first porous structure (100) and the second porous structure (200) weakens or is excessively bonded, making it impossible to exhibit the above advantage. In addition, it may have a negative effect on the formation of the three-dimensional structure (220) and pores (230) of the second porous structure (200).
[0089] Method for manufacturing a porous structure
[0090] A method for manufacturing a porous structure according to one embodiment comprises: (S1) a step of preparing a slurry by mixing and stirring a lithium-affinity polymer, a conductive material, CNTs, and water; (S2) a step of applying the slurry onto a substrate; and (S3) a step of forming a porous structure by placing the substrate coated with the slurry into a water bath containing a non-solvent, wherein R of the non-solvent HSP The value of (Hansen solubility parameter distance) can satisfy between 25 and 29.
[0091] First, to explain step (S1), a slurry (210) can be prepared by mixing a lithium-affinity polymer, a conductive material, CNTs, and a solvent, and then stirring. The slurry (210) may comprise, with respect to 100% by weight of the total, 3 to 20% by weight of the lithium-affinity polymer, 0.4 to 2% by weight of the conductive material, 0.05 to 0.5% by weight of the CNTs, and the remainder being a solvent. The solvent may be water, and R, which will be described later HSP If the equation is satisfied, it is not restricted.
[0092] Specifically, the weight ratio of the constituent materials of the above slurry (210) may comprise, for 100% by weight of the total slurry (210), 4 to 18% by weight, 5 to 16% by weight, 6 to 14% by weight, 7 to 12% by weight of a lithium-affinity polymer, 0.5 to 1.8% by weight, 0.6 to 1.6% by weight, 0.7 to 1.4% by weight of a conductive material, 0.06 to 0.45% by weight, 0.07 to 0.40% by weight, 0.08 to 0.35% by weight, 0.09 to 0.30% by weight, 0.1 to 0.25% by weight of CNT, and the remainder being a solvent. By satisfying the weight percentage of the lithium-affinity polymer, conductive material, and CNT as described above, when the slurry (210) forms a porous structure in a subsequent step, it has the effect of achieving a uniform three-dimensional structure (220), pores (230), and porosity, and ensuring stability.
[0093] As the weight percentage of the lithium-affinity polymer, conductive material, and CNT exceeds the upper limit of the aforementioned range, the density and compactness increase when the slurry (210) forms a porous structure, making it difficult to secure space for the lithium metal (300) to be located or to move, or hindering it. Consequently, there is a problem in that the growth of lithium dendrites and the volume expansion of the lithium metal electrode (400) cannot be effectively reduced. Additionally, as the weight percentage exceeds the lower limit of the aforementioned range, there is a problem in that the compactness and stability decrease when the slurry (210) forms a porous structure.
[0094] A slurry (210) can be prepared by stirring a solution mixed in the above weight ratio at a temperature of 60 to 120°C for 1 to 3 hours. Specifically, the stirring temperature and time may be 70 to 110°C, 80 to 100°C, 85 to 95°C, 1.25 to 2.75 hours, 1.5 to 2.5 hours, or 1.75 to 2.25 hours. However, it is not limited thereto and may be changed within an appropriate range depending on the constituent material of the slurry (210) and the weight ratio of the constituent material.
[0095] (S2) The substrate in step may be composed of at least one of a current collector, a porous substrate, and a first porous structure (100). Specifically, the current collector may be a metal layer such as copper, stainless steel, aluminum, nickel, etc., and may be a metal layer having a conductive coating layer such as a carbon black-based coating layer on its surface. The porous substrate may be a porous structure composed of a polymer or a metallized polymer, etc. The first porous structure (100) is as described above. In addition, the substrate may contain 90% or more of CNTs with respect to 100% of the total weight. However, the type of substrate is not limited thereto, and is not particularly limited as long as it has a porous structure and does not cause chemical changes in the secondary battery and has high conductivity.
[0096] (S2) In the step of applying the slurry (210), a doctor blade, bar coater, comma coater, slot die coater, shutter die coater, etc., may be used. At this time, the thickness of the porous structure can be controlled by adjusting the thickness of the slurry (210). For a detailed description of the thickness of the slurry (210), refer to the description of the thickness of the porous structure mentioned above.
[0097] In step (S3), the non-solvent can penetrate the slurry (210) and the substrate to form a three-dimensional structure (220) and pores (230). At this time, the average diameter and porosity of the pores (230) of the porous structure can be controlled by changing the type of non-solvent. By controlling the average diameter and porosity of the pores (230) simply by changing the non-solvent, the manufacturing process can be simplified and costs can be reduced.
[0098] (S3) In step (S3), the slurry (210) and the substrate may be immersed in a non-solvent tank for 1 to 9 hours. Specifically, it may be 2 to 8 hours, 3 to 7 hours, or 4 to 6 hours. However, it is not limited thereto and may be changed to an appropriate range depending on the type of non-solvent material, the constituent material of the slurry (210), and the weight ratio of the constituent material. By satisfying the aforementioned time range, sufficient exchange between the solvent and the non-solvent is achieved, thereby forming a uniform three-dimensional structure (220) and pores (230). If the upper or lower limit of the aforementioned range is exceeded, there is a problem that the three-dimensional structure (220) and pores (230) are formed unevenly and unstably.
[0099] Non-solvents such as ethanol, 1-butanol, 1-propanol, etc. can be used, and R HSP If the value of the substance satisfies a specific range, it is not limited to this.
[0100] R HSPcan be predicted using the Hansen solubility parameter as shown in the following equation. In this case, the thermodynamic compatibility or relative affinity between the solvent and the non-solvent is the dispersion (δ d ), polarity (δ p ), and hydrogen bonding (δ h ) It can be calculated through the three components of the force. (Here, S represents the solvent and NS represents the non-solvent.) R HSP The value of can be 25 to 29. Specifically, it can be 25.5 to 28.5, 26 to 28, or 26.5 to 27.5. R HSP By satisfying the aforementioned range, the non-solvent can properly penetrate the slurry (210) to achieve a uniform three-dimensional structure (220), pores (230), and porosity. This secures a space where the lithium metal (300) can be located or moved, thereby preventing lithium dendrite growth and volume expansion of the lithium metal electrode (400).
[0101] The above R HSP As the value of deviates from the upper limit, the non-solvent cannot properly penetrate the slurry (210), so a dense porous structure may be formed. In this case, there is insufficient space for the lithium metal (300) to be located or move, so the aforementioned effect may be reduced. In addition, the above R HSP As the value of deviates from the lower limit, the non-solvent may penetrate rapidly and excessively into the slurry (210), resulting in a non-uniform porous structure. In this case, large pores may form inside the porous structure or the surface may become excessively dense, which may reduce the aforementioned effect.
[0102]
[0103] The method for manufacturing a porous structure may further include the step (S4) of removing the porous structure from a non-solvent bath and drying it after step (S3). This allows for the complete removal of the non-solvent and the remaining solvent. Step (S4) may be carried out in a vacuum oven at a temperature range of 40 to 100°C for 1 to 5 hours. Specifically, it may be 50 to 90°C, 60 to 80°C, 2 to 4 hours, or 2.5 to 3.5 hours. However, it is not limited thereto, and the drying method may be changed within an appropriate range depending on the type of non-solvent and solvent.
[0104] lithium metal electrode
[0105] In another embodiment of the present invention, a lithium metal electrode (400) comprising the aforementioned porous structure is provided to prevent lithium dendrite growth and volume expansion of the lithium metal electrode (400) and to provide a high energy density lithium secondary battery.
[0106] Referring to FIG. 1, the lithium metal electrode (400) may include the porous structure described above. For a detailed description of the porous structure, refer to the above. The lithium metal electrode (400) can be manufactured by filling the porous structure with lithium metal (300) by a method such as electrodeposition.
[0107] The lithium metal electrode (400) may have the lithium metal (300) located inside or outside of at least one of the porous structure. The lithium metal (300) may satisfy the following Equations 3 and 4.
[0108] [Equation 3]
[0109] 1 ≤ LME / HCA ≤ 1.3
[0110] [Equation 4]
[0111] -1 ≤ △y / △x ≤ 1
[0112] (In Equation 3 above, LME is the cross-sectional thickness of the lithium metal electrode, and HCA is the cross-sectional thickness of the porous structure, and
[0113] In the above Equation 4, x is the position from left to right of the cross-section of the lithium metal electrode, and y is the height of the lithium metal electrode at x, and
[0114] △y / △x is the ratio of the change in y to the change in x.
[0115] Equation 3 above represents the range of thickness ratios before and after charging the lithium metal (300) into the lithium metal electrode (400). Equation 3 can satisfy 1 to 1.3. Specifically, it can satisfy 1 to 1.25, 1 to 1.2, 1 to 1.18, 1 to 1.17, 1 to 1.16, 1 to 1.15, 1 to 1.14, 1 to 1.13, 1 to 1.12, 1 to 1.11, 1 to 1.10, 1 to 1.09, and 1 to 1.08. By satisfying the aforementioned range of Equation 3, the growth of lithium dendrites and volume expansion of the lithium metal electrode (400) are effectively limited, thereby providing a stable and high-energy-density lithium secondary battery.
[0116] If the above Equation 3 exceeds the upper limit value of the aforementioned range, it means that the volume of the lithium metal electrode (400) expands excessively, which has the problem of not being able to produce the aforementioned effect. In addition, the lower limit value of the aforementioned range, 1, means that there is no change in volume after the lithium metal (300) is charged into the lithium metal electrode (400).
[0117] Equation 4 above represents the uniformity of the surface after charging the lithium metal (300) into the lithium metal electrode (400). In other words, it is a quantitative expression of the fact that lithium dendrites do not grow on the surface of the lithium metal electrode (400). Equation 4 can satisfy -1 to 1. Specifically, it can be -0.8 to 0.8, -0.6 to 0.6, -0.4 to 0.4, -0.2 to 0.2, or -0.1 to 0.1. By satisfying the aforementioned ranges of Equation 4, the surface of the lithium metal electrode (400) is formed uniformly or smoothly, thereby providing a stable high-energy-density lithium secondary battery.
[0118] If the above Equation 4 deviates from the upper and lower limits of the aforementioned range, it implies that lithium dendrites have grown on the surface of the lithium metal electrode (400), which causes a problem in that the aforementioned effect cannot be achieved.
[0119] In addition, the lithium metal electrode (400) can satisfy the following Equations 5 and 6.
[0120] [Equation 5]
[0121] 1 ≤ H2 / H1 ≤ 1.2
[0122] [Equation 6]
[0123] 1 ≤ v2 / v1 ≤ 7
[0124] (H in Equation 5 above n is the thickness of the cross-section of the lithium metal electrode after lithium charging, and v in Equation 6. n Silver thickness H n The lithium charging rate of the lithium metal electrode having the above is the rate, and as n increases, v n The value of is large.)
[0125] The above Equation 5 represents the range of cross-sectional thickness ratios after manufacturing a lithium metal electrode (400) by filling a porous structure with lithium metal (300). Equation 5 may satisfy a range of 1 to 1.2. Specifically, it may be 1 to 1.2, 1 to 1.19, 1 to 1.18, 1 to 1.17, 1 to 1.16, 1 to 1.15, 1 to 1.14, 1 to 1.13, 1 to 1.12, 1 to 1.11, 1 to 1.10, 1 to 1.09, 1 to 1.08, 1 to 1.07, 1 to 1.06, 1 to 1.05, 1 to 1.04, 1 to 1.03, 1 to 1.02, or 1 to 1.01.
[0126] The above Equation 6 represents a range of rate ratios for charging lithium metal (300) into a porous structure. Equation 6 can satisfy 1 to 7. Specifically, it can be 1 to 6.5, 1 to 6, 1 to 5.5, 1 to 5, 1 to 4.5, 1 to 4, 1 to 3.5, 1 to 3, 1 to 2.5, 1 to 2, or 1 to 1.5.
[0127] By satisfying the aforementioned ranges of Equations 5 and 6, when additional lithium metal (300) is charged into the lithium metal electrode (400) which already contains lithium metal (300), changes in lithium dendrite growth and volume expansion may be minimal depending on the speed. In other words, there may be very little difference in lithium dendrite growth and volume expansion between the case of high-speed charging and the case of low-speed charging of lithium metal (300). That is, a high-energy-density lithium secondary battery with stability secured even during high-speed charging and discharging can be provided.
[0128] If the above Equations 5 and 6 exceed the upper limit of the aforementioned range, the volume expansion increases during high-speed charging of the lithium metal (300), and thus the aforementioned effect cannot be achieved. Additionally, the lower limit of the aforementioned range, 1, means that the charging speed of the lithium metal (300) is the same, and therefore the thickness of the lithium metal electrode (400) is also the same.
[0129] lithium secondary battery
[0130] In another embodiment of the present invention, a lithium secondary battery is provided comprising an anode, a cathode, and an electrolyte, wherein the cathode comprises a porous structure manufactured by the method described above.
[0131] The porous structure and the characteristics of the lithium secondary battery derived therefrom are as described above. Furthermore, the battery composition excluding the porous structure is generally known. Therefore, a detailed explanation will be omitted.
[0132] Preferred embodiments and comparative examples of the present invention are described below. However, the following examples are merely preferred embodiments of the present invention, and the present invention is not limited to the following examples.
[0133] Example 1: Porous structure using 1-propanol nonsolvent
[0134] (1) Manufacturing of porous structures
[0135] 1) Preparation of the first porous structure
[0136] A first porous structure in the form of a thin film is prepared by vacuum filtration of a solution containing 0.2 weight% of SWCNT dispersed therein and the remainder being water.
[0137] 2) Preparation of the second porous structure
[0138] PVA polymer, a conductive material (carbon black), and SWCNTs are placed in water. At this time, the mass ratios of the PVA polymer, conductive material, SWCNTs, and water are maintained at 24, 1.6, 0.5, and 276, respectively. The temperature of the mixed solution is raised to 90°C and stirred for 2 hours to prepare a slurry. The slurry is placed onto a first porous current collector and rolled using a doctor blade, then placed in a 1-propanol non-solvent bath for 6 hours to form a second porous structure from the slurry through sufficient exchange between water and 1-propanol. Subsequently, the porous structure is dried in a vacuum oven at 70°C for 3 hours to remove the 1-propanol non-solvent and water, thereby producing a complete porous structure.
[0139] (2) Manufacturing of asymmetric lithium batteries
[0140] 5 mAh / cm² of the structure manufactured in (1) 2 A lithium of a certain capacity is electrodeposited to manufacture an asymmetric lithium battery. At this time, PP (Polypropylene) is used as the separator, and the battery is manufactured using 1 M Lithium bis(trifluoromethane)sulfonimide (LiTFSI) in 1,3-Dioxolane (DOL) / 1,2-Dimethoxyethane (DME) (5 / 5, v / v) + 2 wt% LiNO3 as the electrolyte.
[0141] (3) Manufacturing of LFP lithium complete batteries
[0142] 5 mAh / cm² of the structure manufactured in (1) 2 An LFP lithium complete battery is manufactured by filling it with a certain amount of lithium and using a LiFePO4 cathode. In this case, the separator and electrolyte are the same as those of the above-mentioned lithium asymmetric battery.
[0143] (4) Manufacture of NCM lithium complete battery
[0144] 5 mAh / cm² of the structure manufactured in (1) 2 Fill with lithium of the capacity and LiNi 0.8 Co0.1 Mn 0.1 An NCM lithium complete battery is manufactured using an O2 cathode. At this time, the separator is the same as that of the above-mentioned lithium asymmetric battery, but the electrolyte used is 2 M Lithium bis(fluorosulfonyl)imide (LiFSI) in DME + 1 wt% lithium difluoro(bisoxalato)phosphate (LiDFBP) and 3 wt% LiNO3.
[0145] Example 2: Porous structure using 1-butanol nonsolvent
[0146] (1) Manufacturing of porous structures
[0147] A three-dimensional porous structure is prepared in the same manner as in Example 1, but with 1-butanol as the non-solvent.
[0148] (2) Manufacturing of asymmetric lithium batteries
[0149] An asymmetric lithium battery is manufactured in the same manner as in Example 1, but with 1-butanol as the non-solvent.
[0150] Comparative Example 1: Porous structure using an ethanol non-solvent
[0151] A second porous structure is prepared in the same manner as in Example 1, but with the solvent changed to ethanol.
[0152] Comparative Example 2: Cu foil
[0153] (1) Cu foil
[0154] The thickness typically used corresponds to a Cu foil of 20 μm.
[0155] (2) Manufacturing of asymmetric lithium batteries
[0156] An asymmetric lithium battery is manufactured in the same manner as in Example 1, but using a Cu foil as the electrode.
[0157] (3) Manufacturing of LFP lithium complete batteries
[0158] An LFP lithium complete battery is manufactured in the same manner as in Example 1, but using a Cu foil as the electrode.
[0159] (4) Manufacture of NCM lithium complete battery
[0160] An NCM lithium complete battery is manufactured in the same manner as in Example 1, but using a Cu foil as the electrode.
[0161] Evaluation example
[0162] Evaluation Example 1: Measurement of porosity and electronic conductivity of Example 1, Example 2, and Comparative Example 1
[0163] Figure 2 is a scanning electron microscope (SEM) image confirming the porosity of the porous structures of Example 1, Example 2 and Comparative Example 1.
[0164] Looking at Fig. 2, several large pores are prominent in the cross-section of Comparative Example 1. This is R HSP The cause is that the ethanol nonsolvent with a value of 24.0 penetrated the slurry rapidly, so there was not enough time to form a uniform three-dimensional structure.
[0165] Looking at the cross-section and top surface of Example 1, it can be confirmed that uniform pores and a three-dimensional structure are formed compared to Comparative Example 1. This is due to appropriate R HSP This is due to the 1-propanol nonsolvent having a value of 26.6. On the other hand, it can be observed that Example 2 has smaller and denser pores compared to Example 1, which is due to a relatively high R HSP It is due to 1-butanol nonsolvent having a value of 28.4.
[0166] Figure 3 is a graph showing the porosity of the porous structures of Example 1, Example 2, and Comparative Example 1.
[0167] Specific figures are shown in Table 1 below. When looking at the shape of the graph, Comparative Example 1 has an indistinct maximum peak and a wider full width at half maximum compared to Example 1 and Example 2. This indicates that the three-dimensional structure and pores are not uniform. On the other hand, Example 1 and Example 2 have a narrow and steep graph shape and a very narrow full width at half maximum. Furthermore, it can be seen that Example 1 and Example 2 satisfy the aforementioned ranges of Equations 1 and 2. Through this, it can be seen that a uniform and efficient three-dimensional structure and pores have been secured.
[0168] item Example 1 Example 2 Comparative Example 1 R of the cost sale HSP The value of 24.0 26.6 28.4 Porosity (%) 71.4 42.9 78.4 Diameter at maximum peak (μm) 0.4 0.1 1.0 Half width (μm) 0.40 0.070 1.3 D 20 (μm) 0.30 0.080 0.50 D 30 (μm) 0.35 0.090 0.60 D 70 (μm) 0.60 0.13 1.4 D 80 (μm) 0.85 0.17 1.8 D 70 -D 30 (μm) 0.25 0.040 0.80 D 80 -D 20 (μm) 0.55 0.090 1.3
[0169] Figure 4 is a graph showing the ionic and electronic conductivity of the porous structures of the examples and comparative examples.
[0170] Specific figures are shown in Table 2 below. It can be seen that the second porous structure and the porous structure of Example 1 exhibit superior ionic conductivity compared to the first porous structure of Comparative Example 2 and Example 1. As previously mentioned, this is due to the increased surface area resulting from the three-dimensional structure and pores, and the ionic polymer PVA.
[0171] It can be seen that Comparative Example 1 has the lowest electronic conductivity due to PVA aggregated on the surface and large pores. In contrast, it can be confirmed that Example 1 and Example 2 have high electronic conductivity suitable for practical application. Furthermore, Example 2 has the highest electronic conductivity, which is because it has the lowest porosity and thus high density.
[0172] item Detailed items Ionic conductivity (10 -3 S / cm) Electronic conductivity (10 -2 S / cm) Difference in ionic conductivity with Cu foil (10 -3 S / cm) Example 1 First porous structure 0.0950 0.720 0.008 Second porous structure 0.400 0.250 0.313 porous structure 0.305 0.388 0.218 Example 2 0.262 0.496 0.175 Comparative Example 1 0.360 0.0260 0.273 Comparative Example 2 Cu foil 0.0870 1.36 0
[0173] Evaluation Example 2: Observation of lithium electrodeposition morphology in Example 1 and Comparative Example 2
[0174] FIGS. 5 and 6 show Example 1 and Comparative Example 2 at 1, 3, and 5 mAh / cm², respectively. 2 This is an SEM image of a cross-section of a lithium metal electrode filled with lithium.
[0175] Before lithium electrodeposition, the cross-sectional thickness of Examples 1 and 2 was 80 μm, and the cross-sectional thickness of Comparative Example 2 was 20 μm. Specific values before and after lithium electrodeposition are shown in Table 3 below. Looking at Figures 5 and 6 and Table 3 below, it can be seen that the volume difference before and after lithium electrodeposition in Example 1 is negligible. In addition, it can be seen that Example 1 satisfies the aforementioned range of Equation 3. That is, it can be confirmed that a stable lithium metal electrode was manufactured by effectively preventing lithium dendrite growth through the porous structure.
[0176] item Thickness before electrodeposition (μm) Lithium electrodeposition capacity (mAh / cm²) 2 ) Thickness (μm) after electrodeposition LME / HCA Example 1 80 1 86.3 1.08 3 86.8 1.09 5 87.4 1.09 Comparative Example 2 20 1 27.9 1.4 3 54.6 2.73 5 86.2 4.31
[0177] FIGS. 7 and 8 show Example 1 and Comparative Example 2 at 1 mA / cm 2 This is an SEM image of a lithium metal electrode charged with lithium at a rate of . And Figures 9 and 10 show Example 1 and Comparative Example 2 at 5 mA / cm² 2 This is an SEM image of a lithium metal electrode charged with lithium at a rate. Specific numerical values for this are shown in Table 4 below. Looking at Figures 7 to 10 and Table 4 below, it can be seen that there is no significant difference in volume expansion even with additional low-speed and high-speed lithium charging. Furthermore, it can be seen that Example 1 satisfies the aforementioned ranges of Equations 5 and 6. In other words, it can be concluded that a lithium metal electrode capable of stable and high-speed charging and discharging was manufactured by effectively preventing lithium dendrite growth through a porous structure.
[0178] item Initial lithium electrodeposition capacity (mAh / cm²) 2 ) Lithium electrodeposition rate (mA / cm²) 2 ) v2 / v1 Thickness (μm) after electrodeposition H2 / H1 Example 1 5 1 5 88.9 1.02 5 90.7 Comparative Example 2 1 86.2 1.22 5 105.1
[0179] Evaluation Example 3: Measurement of charge-discharge cycles of asymmetric lithium batteries of Example 1, Example 2, and Comparative Example 2
[0180] Figure 11 is a graph of the charge-discharge cycles of the asymmetric lithium batteries of Example 1, Example 2, and Comparative Example 2.
[0181] A battery is considered to have reached the end of its lifespan when an overvoltage occurs at a peak during the cycle measurement process. Looking at Figure 11, it can be seen that Comparative Example 2 reached the end of its lifespan due to an overvoltage occurring around 70 cycles. On the other hand, it can be seen that Example 2 did not experience an overvoltage up to around 200 cycles, and Example 1 maintained a very stable voltage up to more than 700 cycles. The difference in performance between Example 1 and Example 2 is due to the difference in non-solvents. In the porous structure prepared with 1-butanol as a non-solvent in Example 2, the porosity is low, resulting in a small absolute amount of lithium electrodeposited in the pores. Furthermore, due to the lithium accumulated on the surface of the porous structure, the performance is inferior compared to Example 1.
[0182] Therefore, the full battery cycle measurements of Evaluation Example 4 and Evaluation Example 5 described below were conducted using only Example 1 and Comparative Example 2, which had the best effect.
[0183] Evaluation Example 4: Measurement of charge-discharge cycles of LFP lithium full batteries of Example 1 and Comparative Example 2
[0184] Figure 12 is a graph of the charge-discharge cycles of the LFP lithium full batteries of Example 1 and Comparative Example 2.
[0185] Looking at Fig. 12, it can be seen that Example 1 maintained 80% of its capacity for 490 cycles, whereas Comparative Example 2 maintained 80% of its capacity for only about 100 cycles, and thereafter the capacity decreased significantly.
[0186] Evaluation Example 5: Measurement of charge-discharge cycles of the NCM lithium full batteries of Example 1 and Comparative Example 2
[0187] Figure 13 is a graph of the charge-discharge cycles of the NCM lithium full battery of Example 1 and Comparative Example 2.
[0188] As shown in FIG. 13, Example 1 maintained 80% of its capacity for about 125 cycles, whereas Comparative Example 2 showed a rapid decline in capacity around 50 cycles. In other words, Comparative Example 2 had very poor lifespan and capacity due to electrolyte depletion caused by the formation of large lithium dendrites and side reactions between the lithium metal and the electrolyte. This supports the claim that Example 1 is a lithium metal electrode suitable for high-energy-density lithium secondary batteries with improved lifespan and capacity.
[0189] The present invention is not limited to the above embodiments and can be manufactured in various different forms, and those skilled in the art will understand that the invention can be implemented in other specific forms without changing the technical concept or essential features of the invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. Explanation of the symbols
[0190] 100: 1st porous structure 300: Lithium metal 200: Second porous structure 400: Lithium metal electrode 210: Slurry 220: 3D structure 230: Qi Gong
Claims
Claim 1 A porous structure comprising a lithium-affinity polymer, a three-dimensional structure, and pores, wherein the pores have a full width at half maximum (FWHM) of the pore distribution graph of 0.01 to 1.0 μm and satisfy the following Formula 1. [Formula 1] 0 μm ≤ D 70 -D 30 ≤ 0.50 μm (D in Equation 1 above) I In this, I is the integral value of the above pore distribution graph from 0 μm, and D I is the pore diameter at the point satisfying I.) Claim 2 A porous structure according to claim 1, wherein the porosity of the porous structure is 40 to 75%. Claim 3 In paragraph 2, the porous structure has a porosity of 60 to 75%. Claim 4 delete Claim 5 In claim 1, satisfying the following Equation 2, [Equation 2] 0 μm ≤ D 80 -D 20 ≤ 0.80 μm(D in Equation 2 above) I In this, I is the integral value of the above pore distribution graph from 0 μm, and D I is the pore diameter at the point satisfying I.) Porous structure. Claim 6 A porous structure according to claim 1, wherein the diameter at the maximum peak of the pore is 0.05 to 0.5 μm. Claim 7 In claim 6, a porous structure having a diameter of 0.3 to 0.5 μm at the maximum peak of the pore. Claim 8 A porous structure according to claim 1, wherein the thickness of the porous structure is 5 to 60 μm. Claim 9 (S1) a step of preparing a slurry by mixing and stirring a lithium-affinity polymer, a conductive material, and a solvent; (S2) a step of applying the slurry onto a substrate; and (S3) a step of placing the substrate coated with the slurry into a tank containing a non-solvent to form a porous structure; wherein R of the non-solvent HSP A method for manufacturing a porous structure in which the value of the (Hansen solubility parameter distance) satisfies 25 to 29, and the porous structure satisfies the following Equation 1. [Equation 1] 0 μm ≤ D 70 -D 30 ≤ 0.50 μm (D in Equation 1 above) I In this, I is the integral value of the pore distribution graph from 0 μm, and D I is the pore diameter at the point satisfying I.) Claim 10 A method for manufacturing a porous structure according to claim 9, wherein the slurry comprises, based on 100 weight% of the total, 3 to 20 weight% of the lithium-affinity polymer, 0.4 to 2 weight% of the conductive material, and the remainder being a solvent. Claim 11 In Paragraph 9, R of the above-mentioned cost-effective product HSP A method for manufacturing a porous structure satisfying a value of 25 to 27. Claim 12 In claim 9, the above description comprises at least one of a current collector and a porous substrate, a method for manufacturing a porous structure. Claim 13 A lithium secondary battery comprising: a positive electrode; a negative electrode; and an electrolyte located between the positive electrode and the negative electrode, wherein the negative electrode comprises a porous structure according to any one of claims 1 to 3 and claims 5 to 8.
Citation Information
Patent Citations
Electrode using porous polymer composite scaffold and Li battery comprising the same
KR1020210031451A
